Analisis Kualitas Pelayanan Publik Dalam Proses Persetujuan Berlayar Kapal Perikanan Studi Pada UPT Pelabuhan Perikanan Pantai Mayangan - Faisal Hidan Vidyarna; Renny Candradewi Puspitarini; Mastina Maksin (Universitas Mbojo Bima, 2026)
Public service is one of the government’s primary functions in providing effective, efficient, and transparent services to the public. The sailing permit approval process is one of the most common public services in the maritime sector. A sailing permit is an official document issued to fishing vessels as proof that the vessel meets the administrative and technical requirements for fishing at sea. This study aims to analyze the quality of public services in the process of approving fishing vessels for departure at the Mayangan Coastal Fishing Port (PPP) in Probolinggo City using an explanatory qualitative method. Interviews and observations were conducted with service officers, vessel owners, and crew members using public service quality indicators such as tangibles (physical evidence), reliability, responsiveness, assurance, and empathy to assess the quality of service provided by officers at the Mayangan PPP. This service quality assessment found that public services related to the approval process for fishing vessels at the Mayangan Port and Port Authority (PPP) have generally been carried out satisfactorily, with an average score of . This is evident from the availability of service facilities and infrastructure, clear service procedures, and the staff’s ability to provide information to the fishing community. Efforts are needed to improve service quality by enhancing staff competence, streamlining service procedures, and utilizing digital service systems so that the sailing approval process can be faster, more transparent, and more accountable. It’is hoped that these improvements in service quality will make it easier for fishermen to carry out their fishing activities and support more orderly and sustainable management of the fisheries sector at the Mayangan Fishing Port in Probolinggo City.